MOTIVASI PEREMPUAN BERGABUNG DALAM PARTAI POLITIK - Alip Susilowati Utama (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
Democracy as a political system has necessitated the spirit of equality and togetherness in order to achieve the common good, in the form of state and community life, participation is needed as a form of togetherness and inclusion in the political process. Specifically for women to fulfill the policy requirements of Law Number 10 Year 2008 which requires politics to include a representation of women of at least 30% both founders and central level management. The fact is that based on data from the National Unity and Politics Agency, the presence of women in parliament, especially the Ogan Komering Ulu District DPRD, has decreased from 4 in the 2014-2019 period to 2 in the 2019-2024 period. The purpose of this study was to determine the motivation of women to join political parties. This study used a descriptive qualitative method with a research approach and research focus. This research was conducted at the Office of the United Development Party and the Democratic Party of Ogan Komering Ulu. Primary data sources and secondary data, data collection techniques by interview, observation and documentation. Based on the results of data prosessing in the field about the motivation of women in political parties has been successful because it has fulfilled the needs of political parties, but in a political party there are still thos who use a family or dynastic interest system. The suggestions that can be given to political elites have steps so as not tu use the dynastic system in political parties.